Persepsi Guru Pendidikan Islam Terhadap Ilmu Menurut Konsep Malakah Ilmiyyah Ibnu Khaldun (Sains Humanika, 2018)
The main objective of this study is to identify the Islamic Education teacher (GPI's) perception on knowledge based on its sources and classifications among new GPIs in the State of Selangor. This is descriptive study used a questionnaire as instrument for data collection. The questionnaire was developed based on the concept Malakah Ilmiyyah Ibnu Khaldun through chapter sixth in the Book Muqaddimah. Two constructs are identified as the source of knowledge and classification of knowledge. Using the simple random sampling method, a total of 92 new GPIs was randomly selected from several schools in the Gombak state of Selangor to be a sample of the study. Generally, the study found new GPI perception of knowledge by the concept Malakah Ilmiyyah Ibnu Khaldun is at a high level. All constructs were above 8.0 i.e. sources of knowledge (8.70) and classification of knowledge (8.89). This study showed that the new GPI has a positive perception of practicing naqli and aqli knowledge as taught by Ibnu Khaldun in his Muqaddimah Book. The concept of Malakah Ilmiyyah Ibn Khaldun is actually very consistent to the goal of producing a knowledgeable GPI and at the same time can create a student human capital of the world's brightest and the hereafter. Furthermore, studies on the various concepts still stored in the Muqaddimah script need to be explored, especially in relation to the teaching profession.
Keywords: Islamic education teachers; ibnu khaldun; malakah ilmiyyah; source of knowledge; classification of knowledge